Rehabilitation of executive functioning: An experimental?clinical validation of Goal Management Training - ROBERTSON, IAN (My University, 2000)
Two studies assessed the effects of a training procedure (Goal Management Training, GMT), derived from Duncan?s theory of goal neglect, on disorganized behavior following TBI. In Study 1, patients with traumatic brain injury (TBI) were randomly assigned to brief trials of GMT or motor skills training. GMT, but not motor skills training, was associated with significant gains on everyday paper-and-pencil tasks designed to mimic tasks that are problematic for patients with goal neglect. In Study 2, GMT was applied in a postencephalitic patient seeking to improve her meal-preparation abilities. Both naturalistic observation and self-report measures revealed improved meal preparation performance following GMT. These studies provide both experimental and clinical support for the efficacy of GMT toward the treatment of executive functioning deficits that compromise independence in patients with brain damage.
PUBLISHED
Keywords: Psychology